Morality, Rationality and Academic Dishonesty: A Partial Test of Situational Action Theory - Cochran, John K. (International Journal of Criminology and Sociology, 2015)
This study uses self-report survey data from a sample of college students to provide a partial test of Wikstrӧm’s situational action theory (2010a) by examining the extent, if any, to which the effects of perceptual deterrence on academic dishonesty are moderated by personal morality. The findings show that both personal morality and perceived certainty of formal sanctions are inversely associated with cheating; however, the deterrent effect of high perceived certainty of formal sanctions is not greater among those with weak moral prohibitions against cheating as predicted by Wikstrӧm and observed by Svensson (2015) in an earlier test of Wikstrӧm’s situational action theory.